PENERAPAN METODE GOAL DIRECTED DESIGN UNTUK EVALUASI DAN PERBAIKAN USER INTERFACE DALAM MENINGKATKAN USER EXPERIENCE PADA APLIKASI HESTIBELL - Meisya Jala Girinda; Tan Amelia; Endra Rahmawati (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2022)
Hestibell is a community for everyone to feel valued. The majority of Hestibellits members are women, but men can also join. Hestibell has an application called “Hestibell” which is a platform to support the positive and fun activities held by Hestibell in building a healthy community that can unite members Hestibell with the application, Hestibell can make it easy for members to interact with the features of the Hestibell application to get information on the schedule of activities held every day, get many friends in the community from various cities, make payments when participating in activities, information on loyalty merchandise, cooperate with other parties and information about the community. After conducting interviews with the founders and members of Hestibell, the results showed that the Hestibell application had never been evaluated for the user interface, the appearance of the application was old school, unattractive, the flow of the application was not clear, the application could not develop and compete with other applications. The results of the initial evaluation calculation of the Hestibell application have a mean not reaching 1 so it is included in the "Bad” with the overall indicator average not reaching 1 with the lowest value of -0.92 on the perspicuity and the highest value of -0.29 on the novelty. So that the solution that can be given is to conduct research on evaluation and improvement of user interface using the Goal-Directed Design and User Experience Questionnaire (UEQ) methods. The results of the test with Useberry value mean successful completion of the task was 98% and the click was 39%. Meanwhile, from the final evaluation, it was found that the mean reached 1 with the highest value on the stimulation indicator of 2.02 and the lowest value on the novelty of 1.80 so it entered the "Excellent" criteria. Therefore design user interface of the Hestibell application is acceptable to users.